2010
DOI: 10.1111/j.1464-410x.2010.09548.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the new American Joint Committee on Cancer substratification in node‐negative pT2 urothelial carcinoma of the bladder: analysis of patient outcomes in a contemporary series

Abstract: patients with pT2b UCB had LN-positive disease ( P = 0.02).• The median (range) number of LNs removed in LN-positive disease was 18 (11-30) and in LN-negative disease was 20 (4-38) ( P = 0.52).• In LN-negative disease, actuarial 5-year RFS was 85.9% in patients with pT2a UCB vs 37.5% in those with pT2b UCB ( P < 0.001). Actuarial 5-year CSS was 84.8% in patients with LN-negative pT2a UCB vs 59.6% in patients with LN-negative pT2b UCB ( P = 0.01).• In Cox regression analysis, pT2 substratification was the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…6 In contrast, in 72 patients with pT2 tumors Gakis et al noted 85% CSS for patients with pT2a vs 60% for patients with pT2b tumors. 2 Moreover, a multi-institutional study by Tilki et al in 440 patients with pT2 lymph node-negative disease treated between 1979 and 2008 demonstrated a 5-year CSS of 82.6% for patients with pT2a tumors compared to 70% for those with pT2b tumors. 3 In a risk stratification model in 707 men with pT2N0 bladder cancer treated with radical cystectomy from 1971 to 2008 Sonpavde et al identified a recurrencefree survival HR of 1.7 for pT2a and 3.0 for pT2b when using less than pT2 as a reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In contrast, in 72 patients with pT2 tumors Gakis et al noted 85% CSS for patients with pT2a vs 60% for patients with pT2b tumors. 2 Moreover, a multi-institutional study by Tilki et al in 440 patients with pT2 lymph node-negative disease treated between 1979 and 2008 demonstrated a 5-year CSS of 82.6% for patients with pT2a tumors compared to 70% for those with pT2b tumors. 3 In a risk stratification model in 707 men with pT2N0 bladder cancer treated with radical cystectomy from 1971 to 2008 Sonpavde et al identified a recurrencefree survival HR of 1.7 for pT2a and 3.0 for pT2b when using less than pT2 as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance of these substratifications continue to be debated with conflicting data from large studies in regard to outcome, and pT2 and pT3 substages. [2][3][4][5][6][7][8][9][10][11] To our knowledge none of the studies to date that evaluated the prognostic significance of pathological 1706 www.jurology.com substaging included a centralized pathological review by urological pathologists. In our experience there is interobserver variability in the current definition of pT3 substaging in regard to microscopic vs macroscopic invasion, while an extravesical mass is not well defined.…”
mentioning
confidence: 99%
“…This admission of error by Jewett may have been premature, however, as several recent, large studies found clinical utility in the current pT2a/b staging classification . Gakis et al .…”
Section: Stage Pt2 Carcinomamentioning
confidence: 99%
“…Gakis et al . studied 252 patients with pT2 tumours and found a significant difference in recurrence‐free survival (85.9 versus 37.5%, respectively) and cancer‐specific survival (84.8 versus 59.6%, respectively) between pT2aN0 and pT2bN0 patients . Additionally, pT2 substratification was the only risk factor of recurrence and cancer‐specificity .…”
Section: Stage Pt2 Carcinomamentioning
confidence: 99%
“…In the present study, the only variable associated with a higher risk of LVI was found to be pathological stage (pT1 vs pT2); however, substratification in pT2N0 bladder cancer has also been shown to be of prognostic importance for predicting recurrence after cystectomy [4]. The unknown anatomical extent of lymph node dissection at radical cystectomy makes it difficult to assess the impact of LVI on outcomes because patients with localized tumours and presumed micrometastatic disease (as suggested by LVI) may still be cured with an extended pelvic lymph node dissection [6]. While the authors tried to adjust for this bias by reporting on the number of retrieved lymph nodes, 30% of their patients had < 15 lymph nodes removed at surgery.…”
mentioning
confidence: 99%